Pengaruh Mekanisme Corporate Governance pada Agency Cost - Putri, Made Ayu Mentari; Sukartha, I Made (E-Jurnal Akuntansi; Vol 16 No 1 (2016), 2016)
The purpose of this study was to obtain empirical evidence about the influence of internal and external mechanisms of corporate governance in the agency cost. This research was carried out on non-financial companies listed on the Stock Exchange in 2012-2014. The sampling method using a type of non-probability sampling, with a purposive sampling approach. The sample in this study consisted of 17 observation company. The data analysis technique used in this research is multiple linear regression analysis technique. Based on the results of the analysis can be drawn the conclusion that the variable non-executive directors, executive directors, independent directors, audit committee, institutional ownership and market competition has no effect on monitoring costs, while variable remuneration structure of the debt structure and positive effect on the cost of monitoring. In addition, variable non-executive directors, executive directors, audit committee, institutional ownership and market competition has no effect on bonding costs, while variable independent commissioner, debt structure and remuneration structures have positive influence on the bonding cost. The dependent variable, the variable residual losses only positive effect of debt structure.
Keywords: Agency Cost, Corporate Governance Mechanism